Ambiguity about volatility and investor behavior - Kostopoulos, Dimitrios; Meyer, Steffen; Uhr, Charline (Journal of Financial Economics, 2022)
We relate time-varying aggregate ambiguity about volatility (V-VSTOXX) to individual investor trading. We use the trading records of more than 100,000 individual investors from a large German online brokerage from March 2010 to December 2015. We find that an increase in ambiguity is associated with increased investor activity. It also leads to a reduction in risk-taking, which does not reverse over the following days. Ambiguity averse investors are more prone to ambiguity shocks. These results replicate when using the dispersion of professional forecasters as a long-term measure of ambiguity and are robust when controlling for newspaper- or market-based ambiguity measures.